Postpartum endometritis: experience at a general hospital - Vásquez Teevin, Vicky Angélica (2014)
Objectives: To determine demographic and clinical characteristics of patients with diagnosis of postpartum endometritis at a national hospital. Design: Descriptive, series of cases, retrospective study. Setting: Gynecology and Obstetrics Service, Hospital Nacional Cayetano Heredia (HNCH), Lima, Peru. Participants: Women post partum. Material: Cases with puerperal endometritis from July 2011 through July 2012 were selected from the database of the Epidemiology Unit. Data collected included demographic characteristics, clinical history, risk factors, diagnosis, treatment, evolution and complications. Main outcome measures: Puerperal endometritis cases characteristics. Results: Thirty two cases of puerperal endometritis represented a prevalence of 0.6%. Mean age was 23 +/- 6.2 years, 76% finished high school and 72% were nulliparous. Delivery was by cesarean section in 53% of cases. Most common symptom was fever and the most frequent sign was foul-smelling lochia. Among risk factors, one third of patients underwent more than 5 vaginal examinations, with a máximum of 8; 6 patients had premature rupture of membranes and in 7 meconial amniotic fluid was described. All patients had favorable evolution. Conclusions: Understanding the impact of puerperal endometritis in a general hospital will lead to preventive measures to reduce its incidence by improving anemia prophylaxis and treatment, limiting vaginal exams and promoting biosafety standards.